WIRACARITA: EFFORTS TO INSTILL HINDU VALUES IN EARLY CHILDHOOD - Ni Wayan Sri Rahayu (STAH Dharma Sentana Sulawesi Tengah, 2023)
The educational process given to early childhood both education related to character development, religious education is a basic foundation in forming and building future generations of the nation. These religious and ethical values ​​can be found in various epics. In the teachings of Hinduism there are so many stories or stories that can be used as guidelines or references in developing children's character. The purpose of this study is to explain and examine epics that can be used in the development and inculcation of Hindu values ​​in early childhood. This study uses the literature study method in this case, namely data obtained by conducting studies from various sources of literature. The results of the study show that the inculcation of Hindu religious values ​​in character development in early childhood is very effective, because in Hindu epics there are many stories of heroes who are able to create an attraction for children to listen to, there are also values ​​that can foster a child's character. For example, in the epic Rāmāyaņa which provides a lot of information and learning about moral and ethical values. The inculcation of Hindu religious values ​​in early childhood through Wiracarita is very important, given the increasingly advanced technological developments so it is rare to find parents who tell stories found in Hindu literature and are more focused on using social media such as Youtube.